The Impact of Inclusive Education on Typical Developing Peers in Early Childhood Education Settings: A Systematic Literature Review - Suikkanen, Deborah; Chirchir, Everlyne (My University, 2025)
This study examines the impacts of inclusive early childhood education (ECE) on typically developing peers. The study focuses on their social, emotional, and academic development. The topic of inclusive education has been widely studied, but with a heavy bias towards children with special needs. The purpose of this study was to examine the various aspects of inclusive education by examining the benefits that inclusive education has to offer to typically developing peers. A systematic literature review was conducted, using inclusion and exclusion criteria, and out of an initial 189 articles 15 scientific articles were selected after meeting all the preset requirements of inclusion. The research highlights how inclusive classrooms nurtures empathy, collaboration, and academic engagement in typically developing children while addressing diverse student needs. From the findings, it is evident that inclusive education promotes positive to neutral peer interactions and reduces achievement gaps in diverse learning environments when it is supported by structured teaching interventions, scaffolding, and collaborative activities. Although inclusive education philosophy has numerous strengths, the study acknowledges limitations in the scope of literature language, views of special needs children and contexts. The study also advocates for adopting Universal Design for Learning (UDL) principles and investing in comprehensive policy frameworks to support sustainable inclusive practices. It also highlights the importance raising awareness in the society to address biasness towards inclusive education and the need to equip educators with practical strategies, through professional development programs and provision adequate resources. Mixed method approaches and long-term longitudinal studies, as well as its implementation in low-income and non-Western settings are recommended in order to give comprehensive understanding of the impact of inclusive classrooms beyond ECE level. This study, therefore, contributes to the academic digestion of inclusive education by bringing to light its mutual benefits and its potential to bring about more inclusive and tolerant communities. Key Words: inclusive education, early childhood education, typical peers, and inclusive classrooms
Keywords: inclusive education, early childhood education, typical peers, and inclusive classrooms